Design of New Primer Sets for the Development of a Loop-Mediated Isothermal Amplification for Rapid Detection of Neisseria meningitidis - Cuong Viet Vo; Trang Thu Nguyen; Huong Thu Ngo; Lan Anh Thi Bui; Toan Van Trinh; Loan Thi Vu; Hieu Dang Hoang; Phong Quoc Truong (Current Issues in Molecular Biology, 2025)
Neisseria meningitidis is a pathogenic bacterial agent that causes meningococcal meningitis in humans. Developing a rapid and low-cost N. meningitidis detection method is crucial, especially for developing countries. This study focuses on the development of an efficient loop-mediated isothermal amplification (LAMP) method for accurate N. meningitidis identification. A new LAMP primer set was designed, and a LAMP reaction was optimized. The colorimetric detection method was also applied, and the assay characteristics were evaluated using clinical samples. The results demonstrated a specific LAMP reaction for N. meningitidis detection of genotypes A, B, and C, with a limit of detection of 102 cfu/mL, 100% specificity and sensitivity, and a rapid detection time of only 40 min by colorimetric visual inspection. No cross-reactivity with reference strains of Streptococcus pneumoniae, Staphylococcus aureus, Neisseria lactamica, Mycobacterium tuberculosis, and Haemophilus influenzae type b was observed in the LAMP reaction with the new primer set. This result suggests that the LAMP reaction could be a promising tool for developing a rapid N. meningitidis detection method suitable for use in Vietnam and other developing countries.